Bomb : graphic novel : the race to build--and steal--the world's most dangerous weapon - Sheinkin, Steve; Bertozzi, Nick; Sheinkin, Steve (2023)
Recounts the scientific discoveries that enabled atom splitting, the military intelligence operations that occurred in rival countries, and the work of brilliant scientists hidden at Los Alamos.
Chiefly illustrations.
Keywords: Atomic bomb -- History -- Juvenile literature; Atomic bomb -- History -- Comic books, strips, etc; World War, 1939-1945 -- Secret service -- Juvenile literature; World War, 1939-1945 -- Secret service -- Comic books, strips, etc; World War, 1939-1945 -- Secret service -- Juvenile literature; World War, 1939-1945 -- Secret service -- Comic books, strips, etc; World War, 1939-1945 -- Commando operations -- Juvenile literature; World War, 1939-1945 -- Commando operations -- Comic books, strips, etc; Operation Freshman, 1942 -- Juvenile literature; Operation Freshman, 1942 -- Comic books, strips, etc; Atomic bomb -- History -- Juvenile literature; Atomic bomb -- History -- Comic books, strips, etc; Atomic bomb -- History -- Cartoons and comics; World War, 1939-1945 -- Secret service -- Cartoons and comics; World War, 1939-1945 -- Secret service -- Cartoons and comics; World War, 1939-1945 -- Commando operations -- Cartoons and comics; Operation Freshman, 1942 -- Cartoons and comics; Atomic bomb -- History -- Cartoons and comics; Atomic bomb; Commando troops; Secret service